2022
DOI: 10.3390/vaccines10111822
|View full text |Cite
|
Sign up to set email alerts
|

Digital Information Approach through Social Media among Gen Z and Millennials: The Global Scenario during the COVID-19 Pandemic

Abstract: An infodemic represents a concern for public health, influencing the general population’s perceptions of key health issues. Misinformation is rapidly spread by social media, particularly among young generations. We used data from the WHO “Social Media and COVID-19” study, which was conducted in 24 countries worldwide on over 23,000 subjects aged 18–40 years, to explore Generation Z and Millennials’ models for health-information-seeking behaviors on social media. We summarized data on the most used sources of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…Third, the study contributes to the extant literature on cross-generational studies and consumer behaviour (Blandi et al, 2022;Gumasing and Niro, 2023;Hartijasti and Cho, 2018;Manley et al, 2023;Wahyuningsih et al, 2022). However, this is the first study to incorporate the generational differences of this behavioural model in the food tourism context and it specifically highlights that age plays a moderating role in determining food sharing intentions and future behaviour.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Third, the study contributes to the extant literature on cross-generational studies and consumer behaviour (Blandi et al, 2022;Gumasing and Niro, 2023;Hartijasti and Cho, 2018;Manley et al, 2023;Wahyuningsih et al, 2022). However, this is the first study to incorporate the generational differences of this behavioural model in the food tourism context and it specifically highlights that age plays a moderating role in determining food sharing intentions and future behaviour.…”
Section: Discussionmentioning
confidence: 76%
“…Previous research has stated that there are significant differences between cross-generational cohorts in the use of the Internet to seek digital information (Blandi et al. , 2022) and to share it (Hartijasti and Cho, 2018; Sun and Xing, 2022; Wahyuningsih et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it is important to understand how young adults receive and interpret information regarding COVID-19, as some studies suggest this age group may be extremely hesitant because of perceived low risk of severe outcomes, mistrust in authority and fear regarding side effects especially around infertility and pregnancy outcomes 31–33. A global study found young people were most likely to search for COVID-19 and other health information from social media, raising concerns about exposure to misinformation 34…”
Section: Introductionmentioning
confidence: 99%